Utero-ovarian transposition before pelvic radiation in a patient with rectal cancer: a case report and systemic literature review - Huber, Daniela; Simonson, Colin; Fournier, Ian; Dischl-Antonioni, Irma; Pena Rios, Francisco Javier; Francey, Isaline; Surbone, Anna; Hurni, Yannick (Frontiers in Surgery, 2024)
Objective To describe a case of utero-ovarian transposition (UOT) before pelvic radiation in a patient with rectal cancer and provide a systematic literature review on all reported cases of UOT. Methods We performed a prospective collection and revision of clinical, intraoperative, and postoperative data from a patient who underwent UOT. In addition, a systematic review of the literature available to date on all cases of UOT was realized, and 14 patients from 10 articles were included. Results We reported the case of a 28-year-old nulligravida patient who was diagnosed with a low-grade rectal adenocarcinoma and underwent neoadjuvant chemoradiotherapy, followed by transanal total mesorectal excision (TaTME). Before starting neoadjuvant oncological therapies, the patient underwent laparoscopic UOT. The intervention was performed without complications, and the patient received neoadjuvant oncological treatments as planned. TaTME and uterus repositioning were completed six weeks after the end of radiotherapy. No complications were observed during the first 9 postoperative months. Adequate utero-ovarian perfusion was assessed by Doppler ultrasound, cervicovaginal anastomosis appeared to have healed correctly, and the patient experienced menstrual bleeding. Data from the literature review of all reported cases of UOT were presented and discussed. Conclusions UOT represents a valuable option to preserve fertility in patients requiring pelvic radiotherapy. This study provides additional evidence on the feasibility and safety of performing UOT.